Endogenous mediators in emergency department patients with presumed sepsis: Are levels associated with progression to severe sepsis and death? - Terregino, Carol A.; Lopez, Bernard L.; Karras, David J.; Killian, Anthony J.; Arnold, Gerald K. (Annals of emergency medicine, 2000)
Study Objective: We sought to determine whether levels of the endogenous mediators tumor necrosis factor (TNF)-α, interleukin (IL) 6, and nitric oxide (NO) measured in patients with presumed sepsis (systemic inflammatory response syndrome [SIRS] and infection) are different than levels in patients with presumed noninfectious SIRS, whether levels are associated with septic complications, and whether there are potential relationships between mediators. Methods: A prospective, observational tricenter study of a convenience sample of adults presenting to the emergency department meeting Bone’s criteria for SIRS (any combination of fever or hypothermia, tachycardia, tachypnea, or WBC count aberration) was performed. Mediator levels were determined and associated with deterioration to severe sepsis (hypotension, hypoperfusion, or organ dysfunction) and death in subjects admitted to the hospital with presumed sepsis. Results: One hundred eighty subjects with SIRS were enrolled and classified into 3 groups: group 1 (SIRS, presumed infection, admitted; n=108), group 2 (SIRS, presumed infection, discharged; n=27), and group 3 (SIRS, presumed noninfectious, admitted; n=45). Group 1 TNF-α and IL-6 levels were significantly higher than those found in the other groups. NO levels for groups 1 and 2 were significantly lower than those for group 3. TNF-α and IL-6 levels were higher in the group 1 subjects who had bacteremia or progressed to severe sepsis or death. NO levels were not associated with these outcomes. Conclusion: ED patients admitted with presumed sepsis have elevated cytokine levels compared with patients with sepsis who are discharged and with those patients with presumed noninfectious SIRS. An association appears to exist between cytokines and subsequent septic complications in these patients. The importance of these measures as clinical predictors for the presence of infection and subsequent septic complications needs to be evaluated. [Terregino CA, Lopez BL, Karras DJ, Killian AJ, Arnold GK. Endogenous mediators in emergency department patients with presumed sepsis: are levels associated with progression to severe sepsis and death? Ann Emerg Med . January 2000;35:26-34.]